19 Development of the Puerto Rico Neoplasm and CNS Tumor Registry (PUNCTURE) - Julio Rosado Philippi; Natasha L. Frontera; Aixa de Jesus Espinosa; Valerie Wojna; David Blas Boria; Juan L. Parez-Berenguer; Kimberly Hoang; Ali Alawieh; Miguel Mayol Del Valle (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: To describe and compare clinical data and outcomes for patients with CNS tumors and tumor mimics in Puerto Rico who are undergoing surgical and nonsurgical management. Thus, increasing data from an underrepresented group which can serve as a foundation for investigating determinants of outcomes. METHODS/STUDY POPULATION: This proposal will examine patient charts, radiology and pathology reports, financial data, and treatment details from the electronic medical record of patients receiving surgical and nonsurgical treatment for CNS tumors and mimics in the University of Puerto Rico Medical Sciences Campus and all associated institutions. Data will be analyzed retrospectively between January 1, 2014 and June 30, 2022, and prospectively for ten years until December 31, 2032. Patients with primary and metastatic CNS tumors and tumor mimics in the brain, meninges, ventricles, spinal cord, cranial nerves, orbit, facial sinuses, bony skull, vasculature will be included. The registry will include patients from birth onward. RESULTS/ANTICIPATED RESULTS: We plan to compare different surgical and non-surgical techniques and devices in terms of technical and clinical outcomes after surgical interventions for CNS tumors. We are collaborating with the CNS Tumor Outcome Registry at Emory (CTORE) and plan to continue collaboration with other institutions. Combining our data, we aim to develop predictive models of patient outcomes after surgical and nonsurgical intervention for CNS pathologies using supervised and unsupervised machine learning strategies. DISCUSSION/SIGNIFICANCE: There is a significant lack of literature on CNS intervention outcomes in Puerto Rico. This registry will provide the platform for cost-analysis studies for techniques and clinical protocols applicable to pre-operative, intra-operative, post-operative, and conservative management of patients, in Puerto Rico and beyond.